Literature review: Academic stress of college students during the COVID-19 Pandemic - Prachintya, Vania; Nurcahyo, Firmanto Adi (Insight: Jurnal Ilmiah Psikologi, 2022)
COVID-19 is an infectious disease that has spread widely and has increased throughout the world, including Indonesia. This does not only have an impact on health, the economy, transportation, but also has an impact on the world of education, including higher academic education. As a result of this condition, the government issued various policies in which students were required to take online learning to prevent the transmission of COVID-19. Changes in this system can trigger the emergence of academic stress in students. Academic stress is a reaction that arises in individuals when faced with academic demands. This paper aims to conduct a literature review of studies that explain student academic stress during the COVID-19 pandemic. Literature review was conducted on 7 studies with varying methods and levels of academic stress. The results of the literature review show that the academic stress experienced by students during the COVID-19 pandemic is caused by ineffectiveness during the learning process and the many demands they experience.